Municipal solid waste management in Khulna City Corporation Bangladesh - Hoque, Md. Ikramul; Abdo Qasem, Mohammed Hasan; Parvez, Md. Shohan (Universiti Malaysia Pahang, 2022)
Bangladesh has the eighth-highest population in the world and the sixth-highest population density. In Bangladesh, a 3.09% urban population growth rate is anticipated between 2016 and 2020. Waste management is becoming a bigger issue as a result of the exponential population growth rate, especially in the bigger cities. The amount of trash produced in Bangladesh's cities now is about 25000 tons per day or 170 kg per person each year (as of 2021). Only around 37% of garbage is collected in big cities. However, once this garbage is collected, handling it in a way that is acceptable to society and the environment is difficult. Solid waste management accounts for 15– 25% of the budgets of municipal entities. Incorporating the informal garbage industry in rising cities presents a barrier for effective data collection and analytical management. This essay intends to shed light on Khulna, a significant Bangladeshi city, and its municipal solid waste management system. This study focuses on the municipal solid waste of Khulna City Corporation (KCC) and examines the creation and management status of several types of garbage. It also demonstrates the damaging effects of inadequate garbage management. Finally, it makes some appropriate and costeffective recommendations for trash management.